2018
DOI: 10.1080/00346764.2018.1432884
|View full text |Cite
|
Sign up to set email alerts
|

Robots and us: towards an economics of the ‘Good Life’

Abstract: (Expected) adverse effects of the 'ICT Revolution' on work and opportunities for individuals to use and develop their capacities give a new impetus to the debate on the societal implications of technology and raise questions regarding the 'responsibility' of research and innovation (RRI) and the possibility of achieving 'inclusive and sustainable society'. However, missing in this debate is an examination of a possible conflict between the quest for 'inclusive and sustainable society' and conventional economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The chapter does have the merit to mention less known but very important issues, such as the ethically problematic exploitation of the so-called free "digital labour"users producing the data and information over which tech companies produce their profit-and the challenge of protecting more vulnerable users from various forms of technologically mediated exploitation and manipulation: children, elderly persons, people with mental disabilities. Yet it would have been good to find some more explicit reference to philosophical concepts that might help making sense of-and address these issues, for instance the idea of human mental work as a form of capital to be protected, promoted and rewarded (Naastepad and Mulder 2018), or the idea of applying Amartya Sen's capability approach to digital technology (Oosterlaken 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The chapter does have the merit to mention less known but very important issues, such as the ethically problematic exploitation of the so-called free "digital labour"users producing the data and information over which tech companies produce their profit-and the challenge of protecting more vulnerable users from various forms of technologically mediated exploitation and manipulation: children, elderly persons, people with mental disabilities. Yet it would have been good to find some more explicit reference to philosophical concepts that might help making sense of-and address these issues, for instance the idea of human mental work as a form of capital to be protected, promoted and rewarded (Naastepad and Mulder 2018), or the idea of applying Amartya Sen's capability approach to digital technology (Oosterlaken 2013).…”
mentioning
confidence: 99%
“…However, the book could have been enriched by some more suggestion for new concepts and theories within the Western tradition to guide a future AI Ethics. Might we, for instance, need new concepts of privacy (Taylor et al 2017), capital (Naastepad and Mulder 2018), democracy (Bernholz et al 2021), control (Santoni de Sio and van den Hoven 2018), justice (Nagenborg 2009), responsibility (Santoni de Sio and Mecacci 2021)…? And, from a more methodological point of view, if current concepts of Responsible Innovation (Stilgoe et al 2013) and Design for Values (van den Hoven et al 2015) have shown some limitations, how can they be revised and integrated (Blok 2014;Kiran 2012)?…”
mentioning
confidence: 99%
“…Such prospects raise questions regarding the normative economic principle that has been assigned to give direction to capital, influencing in turn which technological and technical developments get funding . When guided by homo economicus, technology tends to be used as the handmaiden of the (neoclassical) principle of profit maximisationor its modern version, maximisation of shareholder valuewhich considers human physical and intellectual work as a cost to be minimised; technological un(der)employment and an erosion of the human mind are two important potential social and cultural consequences (Naastepad and Mulder 2018).…”
Section: Humanity's 'Permanent Problem'mentioning
confidence: 99%
“…is the remuneration of the (time-intensive) work of doctors, nurses, teachers, therapists, judges, artists, etc., efforts are directed at reducing this work mainly through standardisation, automation and robotisation. As a consequence, the natural tendency of work in these realms to increase is reversed (Naastepad 2019;Naastepad and Mulder 2018).…”
Section: Humanity's 'Permanent Problem'mentioning
confidence: 99%
“…In the face of this reticence to curtail working hours, the last couple of years have given rise to profound anxiety about the disruptive effects of new digital automation technologies and the prospect of sweeping downsizing in the availability of work (McClure, 2018;Naastepad and Mulder, 2018). Specifically, societal diffusion of artificial intelligence, general-purpose robots and self-driving vehicles is threatening to sharply diminish demand for labour and lead to a future of large-scale unemployment.…”
Section: Introductionmentioning
confidence: 99%